LECTURER’S POLITENESS IN TEACHING LEARNING INTERACTION (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study analyze politeness used by lecturers during the learning process takes place. It was found that teachers apply the principles of politeness and politeness strategies in managing the classroom. The goal is to preserve the image of students and to get cooperation from the students. Politeness is the best expression of the practical application of good manners, and also the way to show appreciation from one person to another, but it is difficult to study because it does not involve the understanding, but also socio-cultural values of the society. This is a study of lecturers’ politeness strategies in interaction of teaching and learning in the Faculty of Teacher Training and Education, PGRI Mahadewa University
Keywords: Politeness; Politness Principle; Politness Strategies